Drives of Agricultural Entrepreneurship: A Scoping Review - Nadapdap, Hendrik Johannes; Suharno, Suharno; Fariyanti, Anna; Syaukat, Yusman (Universitas Panji Sakti, 2025)
Agricultural entrepreneurship has the potential to drive economic development. Identifying the factors that influence the orientation towards agricultural entrepreneurship can aid in designing intervention programs that encourage farmers to develop entrepreneurship in the agricultural sector. This study aims to review scholarly articles related to the factors that promote entrepreneurial orientation in the agricultural field. A Scoping Review was conducted with the following eligibility criteria: a) academic articles from Scopus, Science Direct, Ebsco, and Wiley, b) articles published within the last 10 years, from 2015 to 2024, c) written in English, d) the study population are farmers, and e) the measured impact is agricultural entrepreneurship. Article management was done using Mendeley with a four-stage article selection process, including identification, screening, eligibility, and inclusion. Over the past 10 years, there have been 12 articles related to the factors driving farmers' entrepreneurial orientation, with seven variables most frequently identified: knowledge support, market access, networks, association membership, experience, risk-taking, access to internet, and radio. Knowledge support provides crucial information and skills for decision-making and opportunity utilization. Market access enhances farmer entrepreneurship by providing information and value-added services. Participation in farmer associations improves skills, information access, business mindset, and technology adaptation. Experience and risk-taking form a strong foundation for entrepreneurial behavior, enabling the identification of opportunities, development of innovative solutions, and risk management. Access to the internet and radio serves as a medium for farmers to obtain agricultural information.